2004
DOI: 10.1016/j.jvs.2003.08.038
|View full text |Cite
|
Sign up to set email alerts
|

Leg strength in peripheral arterial disease: associations with disease severity and lower-extremity performance

Abstract: Among patients without prior leg revascularization, strength in each leg is highly correlated with the lower-leg ABI. Leg strength is associated independently with functional performance. Further study is needed to determine whether lower-extremity resistance training improves functioning in patients with peripheral arterial disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
97
0
16

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(116 citation statements)
references
References 30 publications
3
97
0
16
Order By: Relevance
“…These findings suggested that diminished bioenergetic reserve (Schrack et al ., 2013) and/or impaired bioenergetic synthetic capacity is in part responsible for slower walking speeds in older persons. This hypothesis is consistent with the progressive decline in muscle mass and strength (with the decline in strength outpacing that of muscle mass) (Goodpaster et al ., 2006; Newman et al ., 2006) often observed in older persons and attributed in part to higher prevalence of chronic diseases (McDermott et al ., 2004) and lower physical activity in older compared with younger persons (Cesari et al ., 2009). …”
Section: Introductionmentioning
confidence: 99%
“…These findings suggested that diminished bioenergetic reserve (Schrack et al ., 2013) and/or impaired bioenergetic synthetic capacity is in part responsible for slower walking speeds in older persons. This hypothesis is consistent with the progressive decline in muscle mass and strength (with the decline in strength outpacing that of muscle mass) (Goodpaster et al ., 2006; Newman et al ., 2006) often observed in older persons and attributed in part to higher prevalence of chronic diseases (McDermott et al ., 2004) and lower physical activity in older compared with younger persons (Cesari et al ., 2009). …”
Section: Introductionmentioning
confidence: 99%
“…2,3 The aging process results in decreased muscle function, 4,5 which has been associated with an increased risk of falls, 6,7 leading to impairments in daily activities. 7,8 In PAD patients, aside from the effects of aging, lower-extremity strength deficits are associated with walking impairment, 9 reduced physical functioning, poor capacity for walking faster, and reduced stair-climbing ability. 3 Muscle function, which is related to physical function and functional disability in subjects with different clinical conditions, has been accurately assessed with isokinetic dynamometers.…”
Section: Introductionmentioning
confidence: 99%
“…El deterioro funcional de estos pacientes está relacionado fundamentalmente con los valores basales del ITB. El 9% de los pacientes con una presión sanguínea en el tobillo entre 40-60 mmHg o un ITB <0,5 progresarán a isquemia crítica en el primer año tras el diagnóstico (10 (15) .…”
Section: Figura 1 Clasificación De Fontaine Y Rutherfordunclassified